Effect of Exchange Rate Misalignment on Bilateral Trade Between Kenya and European Union: 2000-2016 - Charles Munene Gachoki; Susan Okeri; Julius Korir (European Scientific Journal, ESJ, 2021)
The exchange rate is an important variable in international trade because a country's competitiveness is determined by the expectations on how trade reacts to its movements. To orient the economy outwards, Kenya has pursued various measures from the 1990s to the 2000s. Kenya also signed up for nonreciprocal trade with the European Union under the Cotonou agreement. Despite the export-oriented efforts, Kenya's trade has remained skewed towards imports and a widening trade deficit which seems to follow the weakening of the Kenya shilling. The main policy dilemma therefore, is how imports accelerated in an environment of unhindered European Union market access, hence the motivation of this study. The study adopted a dynamic modeling approach since previous and present values affect exchange rate and trade. The results show that the economic fundamentals drive the real exchange rate. In terms of misalignment, the exchange rate is overvalued to a maximum of 5.9 percent and undervalued up to 5.2 percent. The estimated misalignment hurts imports but has a positive, statistically insignificant effect on exports. The results of this study suggest that the monetary authority should ensure the exchange rate remains stable and within the 6 percent range while monitoring all the underlying determinants. Additionally, hedging instruments should be made available and affordable to traders.